2021
DOI: 10.21037/atm-21-1666
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of combination antiviral treatment with extended duration for hepatitis B e antigen (HBeAg)-negative chronic hepatitis B in China

Abstract: Background: Hepatitis B surface antigen clearance or seroconversion is rarely achieved for patients using nucleoside analogs or pegylated interferon alpha monotherapy approaches. Several recent studies have confirmed the benefit of a combination of these two approaches for selected chronic hepatitis B patients.However, few reports have investigated long-term outcomes or health economic evaluation for hepatitis B surface antigen clearance. The aim of this study was to perform a cost-effectiveness analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Expanding the treatment indications for CHB and increasing the coverage of available treatments are highly effective and cost-effective strategies to reduce adverse outcomes related to CHB [ 38 ]. Combining NAs with PegIFNα and extending the treatment duration in current therapeutic regimens have been shown to prolong quality-adjusted life-years, making it more cost-effective than NAs monotherapy [ 39 ]. Ongoing real-world studies with large sample sizes and multicenter participation are focused on achieving functional cure for CHB patients and reducing the incidence of liver cancer [ 15 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expanding the treatment indications for CHB and increasing the coverage of available treatments are highly effective and cost-effective strategies to reduce adverse outcomes related to CHB [ 38 ]. Combining NAs with PegIFNα and extending the treatment duration in current therapeutic regimens have been shown to prolong quality-adjusted life-years, making it more cost-effective than NAs monotherapy [ 39 ]. Ongoing real-world studies with large sample sizes and multicenter participation are focused on achieving functional cure for CHB patients and reducing the incidence of liver cancer [ 15 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of date, IFN remains the main drug for the functional cure of hepatitis B. IFN can achieve a higher functional cure rate in treating e‐antigen‐negative CHB or HBsAg in inactive HBsAg carriers. The lower the baseline HBsAg level, the higher is the chance of achieving a functional cure 22,23 . The functional cure rate in patients with e antigen‐positive CHB is still a clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…The lower the baseline HBsAg level, the higher is the chance of achieving a functional cure. 22,23 The functional cure rate in patients with e antigen-positive CHB is still a clinical problem. Li et al 24 compared the therapeutic efficacy of three strategies, including TDF monotherapy, peg-IFNα add-on therapy, and de novo combination therapy, in HBeAg-positive naïve patients; the rates of HBsAg seroconversion were still low and not significantly different among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…The treat-IT strategy was preferred to the untreat-IT strategy when the annual HCC incidence was higher than 0.54% based in a cost-effectiveness threshold of USA$20,000/QALY from a healthcare system perspective. 35 In a Chinese population, Chen et al 36 reported that combination therapy with NAs and PEG-IFN-α for HBeAg-negative patients with HBsAg ≤1,000 IU/mL not only increased the QALYs, but also reduced medical costs and was more cost-effective than NAs monotherapy.…”
Section: Financial Cost-benefit Of Antiviral Therapymentioning
confidence: 99%
“… 35 In a Chinese population, Chen et al . 36 reported that combination therapy with NAs and PEG-IFN-α for HBeAg-negative patients with HBsAg ≤1,000 IU/mL not only increased the QALYs, but also reduced medical costs and was more cost-effective than NAs monotherapy.…”
Section: Financial Cost-benefit Of Antiviral Therapymentioning
confidence: 99%